Suppressing wind-induced bending and torsional vibrations of long-span bridges by series-type tuned mass damper inerters (STMDIs). (February 2023) - Li, Zhenchuan; Xu, Kun; Bi, Kaiming; Xu, Li; Han, Qiang
Abstract: This study proposes to use series-type tuned mass damper inerters (STMDIs) to suppress the bending and torsional vibrations of the bridge girder. Three potential layout schemes of STMDIs suitable for being installed inside the bridge girder are investigated. The governing equations of the bridge with spatially distributed STMDIs are established in modal coordinate. The optimal design strategy for suppressing the multiple-mode vibration of the bridge girder by using spatially distributed STMDIs is proposed. The feasibility of these schemes is validated and compared in terms of control efficiency, space feasibility, and frequency band property. Time-domain validation through embedding the STMDIs into the finite element model of the bridge is also conducted. The results show that STMDIs have a much better control efficiency and frequency band property than TMDI and TMD. It can simultaneously be tuned to suppress the bending and torsional vibrations of the bridge at different bending-to-torsional frequency ratios. And the space performance of this device is also quite favorable. Through spatially distributing the multiple STMDIs, the vibration of the bridge can be further reduced.